2021
DOI: 10.3390/nano11123233
|View full text |Cite
|
Sign up to set email alerts
|

Complex Tumor Spheroid Formation and One-Step Cancer-Associated Fibroblasts Purification from Hepatocellular Carcinoma Tissue Promoted by Inorganic Surface Topography

Abstract: In vitro cell models play important roles as testbeds for toxicity studies, drug development, or as replacements in animal experiments. In particular, complex tumor models such as hepatocellular carcinoma (HCC) are needed to predict drug efficacy and facilitate translation into clinical practice. In this work, topographical features of amorphous silicon dioxide (SiO2) are fabricated and tested for cell culture of primary HCC cells and cell lines. The topographies vary from pyramids to octahedrons to structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…This is the case of inert silicon dioxide (SiO 2 ) substrates decorated with fractal-like structures of varied morphology, i.e., from pyramids and octahedrons to fractals of increased hierarchy organised in periodic arrays. These arrays enable surface topography, which can be arrayed, adopting a hexagonal (Hex) configuration [ 11 ], as shown in Fig. 1 , highlighted by the yellow arrow and hexagon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case of inert silicon dioxide (SiO 2 ) substrates decorated with fractal-like structures of varied morphology, i.e., from pyramids and octahedrons to fractals of increased hierarchy organised in periodic arrays. These arrays enable surface topography, which can be arrayed, adopting a hexagonal (Hex) configuration [ 11 ], as shown in Fig. 1 , highlighted by the yellow arrow and hexagon.…”
Section: Resultsmentioning
confidence: 99%
“…Fractals are known for their high level of organisation, functional morphology, and similarity over a range of dimensional scales. These topographical architectures with increased hierarchy have successfully been used for the differentiation of intestinal tumour cells [ 10 ], as well as the formation of complex tumour spheroids [ 11 ]. Due to their multiscale geometry with a set of characteristic distances ranging from a few micrometers lattice spacing down to 500 nm features [ 12 ], fractal-like inorganic architectures arrayed over a substrate can serve as biomimetics, such as tissue and wound healing applications.…”
mentioning
confidence: 99%
“…As mentioned previously, the microstructured fractal substrates are of particular interest in cell biology due to their capacity to modulate the cell phenotype and behaviour. This was successfully used to isolate cell lines, promote tumor growth and drive cell differentiation in a fast and reliable way [14, 16]. More generally, 3D substrates open promising perspectives to produce complex in vitro models faithfully mimicking cell behaviours in tissues that can be subsequently used for a range of applications, particularly in the domain of drug screening and toxicity measurements.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the differentiating HT29 colon cancer line forms a 2D cell layer. It has previously been observed that primary tumour cells with cancer-associated fibroblasts and hepatocellular carcinoma cell lines such as HLF form on the same G1 spheroids [45]. It seems that on the topographic substrates, the cell growth is supported in its natural form.…”
Section: Discussionmentioning
confidence: 96%